Band gap narrowing induced by oxygen vacancies in reactively sputtered TiO2 thin films - Mesoudy, Abdelouadoud El; Machon, Denis; Ruediger, Andreas; Jaouad, Abdelatif; Alibart, Fabien; Ecoffey, Serge; Drouin, Dominique (Thin solid films, 2023)
•TiO2 thin films were deposited by reactive magnetron sputtering.•Oxygen vacancy concentration was modulated by tuning the oxygen partial pressure.•Oxygen vacancies concentration narrows the optical bandgap of TiO2 films. Amorphous TiO2-x thin films were deposited using direct current reactive magnetron sputtering. It was possible to tune the defect concentration by controlling the oxygen flow rate during the deposition process. The operating deposition regime has a significant influence on the properties of the TiO2-x film. The refractive index was found to decrease with increasing oxygen flow rate, which was essentially related to changes in film density. Besides this, increasing the oxygen vacancy defect concentration induced a slight decrease in the optical bandgap, as well as widening of the defect's Urbach band tails near the conduction band edge. For TiO2-x films deposited in oxygen-deficient conditions, the decrease in optical bandgap and widening of Urbach tails induced the shift of the Fermi level towards the conduction band, which enhanced the concentration of the charge carriers.